Respuesta :
Answer:
The answer is x=9 and y=1
Step-by-step explanation:
First, you have to substitute x from -4x to 9y which is -4(9y).
That would equal -36y.
Then the second equation would look like this:
-36y + y = -35
Then simplify. If you add -36y and y, it would equal -35y.
-35y = -35
Divide -35 on each side.
y = 1
To find the x value, you have to plug 1 into the first equation. (It doesn't matter which equation you plug into).
So if you plug it into the first equation it would look like this:
9(1) = x
9 = x